Metal-organic framework-enabled pesticides are an emerging tool for sustainable cleaner production and environmental hazard reduction. (1st November 2022) - Vasseghian, Yasser; Arunkumar, Priya; Joo, Sang-Woo; Gnanasekaran, Lalitha; Kamyab, Hesam; Rajendran, Saravanan; Balakrishnan, Deepanraj; Chelliapan, Shreeshivadasan; Klemeš, Jiří Jaromír
Abstract: Two of the most important challenges of the new millennium are the sustainability of agricultural output and the security of global food supplies. The ability of agro-ecosystems to adapt to a rapidly changing climate and improve the global food supply while limiting unintentional environmental damage is critical to addressing these issues. Nanomaterials that can encapsulate and transport active pesticide ingredients (AIs) responsively (e.g., regulated, targeted, and synchronized) offer new opportunities to improve the efficacy and efficiency of traditional pesticides. Completed analysis of the essential traits of nanopesticides in pest management for crop enhancement in comparison to their non-nano scale analogues for sustainable, cleaner production. Cleaner production projects contribute to sustainable development through the development of novel and smart technologies. Nanopesticides outperform non-nano size pesticides in terms of total efficacy against target organisms by 32%, including a 19% improvement in outdoor studies. Notably, the toxicity of nanopesticides is 43.2% lower for non-target organisms, showing a reduction in environmental collateral damage. A 22.2% decreased potential for leaching of AIs into soils is combined with a reduction of 41.5% in the premature loss of AIs before reaching target organisms (Wang et al., 2022 ). This study seeks to answer the question of how the use of nanopesticides can lead to improved sustainable cleaner production. This study focused on the characteristics of numerous non-nanoscale analogues to a wide spectrum of nanopesticides used to manage agricultural pests. Also, to address several new biotic and abiotic threats in a constantly changing climate, the responsive nanoscale platform is given special consideration. Pesticide particles smaller than 500 nm are referred to as nanopesticides in this investigation. The benefits of nanopesticides can lead to an increase in agricultural yields, which can support sustainable agriculture and help ensure global food security. Graphical abstract: Image 1 Highlights: Nanopesticides are a good platform towards sustainable cleaner production. Pesticidal nanoformulations outperform traditional insecticides in terms of efficacy. Nanopesticides lead to a significant reduction of environmental pollutants. Nanopesticides ensure sustainable agriculture.